The Impact of Out-of-Hours Presentation on Clinical Outcomes in ST-Elevation Myocardial Infarction - Biswas, S.; Brennan, A.; Duffy, S.J.; Andrianopoulos, N.; Chan, W.; Walton, A.; Noaman, S.; Shaw, J.A.; Ajani, A.; Clark, D.J.; Freeman, M.; Hiew, C.; et al. (ELSEVIER SCIENCE INC, 2020)
Background: Systems of care have been established to ensure patients with ST-elevation myocardial infarction (STEMI) get timely access to primary percutaneous coronary intervention (PPCI). In this study, we evaluated whether patients undergoing PPCI both in-hours and out-of-hours experience similar care and clinical outcomes. Methods: Of 9,865 patients who underwent PCI for STEMI from 2005 to 2016 and were enrolled in the multi-centre Melbourne Interventional Group registry, patients who had initially presented to a non-PCI capable hospital, received thrombolysis or presented >12 hours post-symptom onset were excluded. Our final study cohort of 4,590 patients were dichotomised by whether PPCI was performed in-hours or out-of-hours, and compared. The primary outcome was 30-day mortality. Results: The in-hours group included 1,865 patients (40.6%) while 2,725 patients (59.4%) had out-of-hours PPCI. Patients presenting out-of-hours had longer median door-to-balloon time (DTBT; 83 [IQR 61–109] vs. 60 [IQR 41–88] mins, p < 0.01) and were more likely to receive a drug-eluting stent (p = 0.001). Procedural characteristics were otherwise similar although rates of radial access were low overall (18.4%). No differences in in-hospital, 30-day or 12-month mortality were observed between the groups (p = NS). On Cox proportional hazards modelling, out-of-hours presentation was not an independent predictor of 30-day mortality (HR 0.94, 95% CI 0.71–1.22). A landmark analysis of data from 2012 did not change the primary outcome. Conclusion: Despite a slightly longer DTBT, patients undergoing PPCI out-of-hours experienced similar care and clinical outcomes to the in-hours group. Given the majority of patients with STEMI present out-of-hours, these data have implications for STEMI systems of care.